Synthesis and structural analysis of cis-bis(1,10-phenanthroline)dicarbonyl ruthenium(II) 1.72-trifluoromethanesulfonate 0.28-hexafluoridophosphate - Takase, Tsugiko; Oyama, Dai (European Journal of Chemistry, 2021)
Ruthenium(II) complexes containing both 1,10-phenanthroline (Phen) and carbonyl (CO) ligands are important molecules for various applications including catalysis. In this work, the molecular structure of [Ru(Phen)2(CO)2]2+ was determined via X-ray diffraction analysis for the first time. The complex exhibits substitutional disorder of one of counter-anions in the asymmetric unit, with different occupancies for CF3SO3- (0.72) and PF6- (0.28). The ruthenium atom is coordinated in a distorted octahedral environment by two carbonyl carbon atoms and four nitrogen atoms from bis-Phen ligands. The cation displays a cis configuration of the carbonyl ligands. Several hydrogen bonds and π-π interactions are present in the crystal. In addition to structural characterization, IR spectral data for the complex is compared with calculated values. These results provide fundamental data for understanding various properties of related ruthenium complexes.